A PA6T66 molding composition and its application

By using the PA6T66 molding composition, the LED reflective bracket material is solved, and the contrast and grayscale insufficient at high temperature is achieved, and the effects of high contrast, high grayscale, good hardware adhesion and low blue light are achieved, improving the display effect and reliability of the LED display screen.

CN117887254BActive Publication Date: 2025-04-08ZHUHAI WANTONG SPECIAL ENG PLASTICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410163671.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-29
Publication Date
2025-04-08
Estimated Expiration
2040-12-29

AI Technical Summary

Technical Problem

The existing LED reflective bracket materials are prone to deform when used at high temperatures, and the contrast and grayscale are insufficient, making it difficult to meet the mechanical strength and fluidity requirements of small-pitch displays. At the same time, the hardware is poorly adhered to, which affects the reliability and picture quality of LED displays.

Method used

Using PA6T66 molding compositions, including PA6T66 resin, wollastonite and toner, the whiteness and reflectivity of the material are controlled, and the adhesion to hardware is improved and blue light is reduced by adjusting the 6T/66 unit ratio, end carboxylic content and distribution size of wollastonite.

Benefits of technology

The LED display light source reflection bracket is realized with high contrast, high grayscale, good hardware adhesion and low blue light, improving the display effect and reliability of the LED display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a PA6T66 molding composition, which is mainly achieved by controlling the content of 6T units in the PA6T66 repeating unit to be 45-65 mol%, the content of 66 units to be 35-45 mol%, controlling the diameter of wollastonite in the PA6T66 molding composition to be 4-8 μm but not including 8 μm, the length to be 10-100 μm but not including 100 μm, adjusting the whiteness of the polyamide molding composition to be less than 30, and the reflectivity of the 460nm light source to be less than 7%. The PA6T66 molding composition of the present invention has the advantages of high contrast and grayscale, reduced blue light, and good adhesion between plastic and hardware, and can meet the requirements of packaging process and long-term reliability. As a LED display light source reflection bracket packaging product, it can be used to manufacture high-contrast LED display screens for multi-scene applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a PA6T66 molding composition and application thereof. Background Art

[0002] LED light sources are mainly composed of semiconductor chips, LED light source reflective brackets, gold wires, and packaging glue. The LED light source reflective bracket is the "skeleton" of the LED light source and is also a functional part. The LED packaging process requires solid crystal, wire bonding, and packaging glue curing, and other materials and components are integrated here. The LED reflective bracket needs to reflect the light emitted by the LED chip at a certain angle to reduce light loss, and then pass it through packaging materials such as epoxy resin or silicone to form a light source for LED lighting or display. The LED reflective bracket material is a core material for LED lighting, which is directly related to the performance and life of the LED light source.

[0003] At this stage, the material selection of LED reflector bracket needs to consider the following points:

[0004] First, during the entire packaging process, the LED reflective bracket needs to be exposed to a temperature of 150-200°C for 6-10 hours. At the same time, the packaged lamp beads need to undergo SMT when they are made into display screens. It is required that the LED bracket or lamp beads will not be deformed during packaging and SMT, and will not be damaged under load. The heat resistance and mechanical strength of the LED bracket material are required to be high.

[0005] Second, in recent years, the light source of LED display screens has gradually developed towards small-pitch display screens with a dot pitch below P2.5, which has made the research and development and manufacturing of LED display screens constantly face huge challenges in this process. The manufacturing of small-pitch display screen brackets has gradually developed towards thin walls, multiple mold cavities, and small sizes, which has put forward more stringent requirements on the fluidity, ultra-multi-cavity formability, and mechanical strength of LED reflective bracket materials.

[0006] Third, during the use of LED lamps or displays, due to different environments, they are often affected by severe weather such as high temperature, typhoons, heavy rain, lightning, etc. In order to keep the lamps or displays safe in severe weather and to prevent the light source from failing in various environments, high requirements are placed on the tightness of the plastic and hardware used in the LED reflective bracket.

[0007] Fourth, in the field of LED display applications, in order to display clear and sharp picture quality, the brightness and contrast of the display screen is a very important indicator. At present, the main solution used in the market is the LED bracket produced by pure white LED reflective material, and the surface needs to be silk-screened with black ink. The process is cumbersome, affects efficiency, and is costly, but the side and reflective cup surface are still white, which reduces the contrast and grayscale of the LED display screen.

[0008] Fifth, about the light source: On the one hand, the wavelength that the average person's eyes can perceive is between 780 and 400nm. Among them, blue light is light with a wavelength between 400nm and 480nm. Short-wave blue light with a wavelength of 400 to 450nm is the most harmful to the retina. This wavelength of blue light will increase the amount of toxins in the macula of the eye, seriously threatening people's eye health. On the other hand, the light source of the LED full-color display is packaged by three chips: red (R), green (G), and blue (B). Among them, the blue light chip has the lowest brightness, that is, the contrast is the highest, so the LED light source bracket for the blue light reflectivity of the chip will directly affect the overall contrast of the LED display. The highest degree. LED screen anti-blue light has been popularized to various mobile phones and TV LED screens, but the general measure is to coat the screen surface with an anti-blue light film, but this measure has the defects of fragile film and high cost.

[0009] Those skilled in the art mainly focus on the first and second points above to improve the materials of LED reflective brackets, but rarely touch upon the problem of the tightness between the materials used in the LED brackets and the bracket hardware, and improving the contrast and grayscale of the LED display brackets. Summary of the invention

[0010] The object of the present invention is to provide a PA6T66 molding composition having the advantages of high contrast, high grayscale, good adhesion to hardware, and reduced blue light.

[0011] Another object of the present invention is to provide a use of the polyamide molding composition.

[0012] The present invention is achieved through the following technical solutions:

[0013] A PA6T66 molding composition, comprising the following components in parts by weight:

[0014] 40-70 parts of PA6T66 resin;

[0015] Wollastonite 30-60 parts;

[0016] Color powder 0.4-5 parts;

[0017] Based on the molar percentage of PA6T66, the 6T unit content is 45-65mol%, the 66 unit content is 35-55mol%, the terminal carboxyl content of the PA6T66 is 20-110 mol / t, and the number average molecular weight range is 7000-17000;

[0018] The average diameter of wollastonite in the PA6T66 molding composition is 4-8 μm but not including 8 μm, and the average length is 10-100 μm but not including 100 μm;

[0019] The whiteness of the polyamide molding composition is less than 30, and the reflectivity of the 460nm light source is less than 7%.

[0020] Preferably, the wollastonite content is 40-55 parts.

[0021] The preferred ratio of 6T / 66 units is, based on the molar percentage of PA6T66, 50-65 mol% of 6T units and 35-50 mol% of 66 units.

[0022] The number average molecular weight range of PA6T66 that can achieve the purpose of the present invention is 1000-30000; preferably, the number average molecular weight range of PA6T66 is 7000-17000.

[0023] The terminal carboxyl content of the PA6T66 resin that can achieve the purpose of the present invention is 20-110 mol / t; preferably, the terminal carboxyl content of the PA6T66 resin is 35-80 mol / t.

[0024] The PA6T66 resin of the present invention may be a commercially available product, or may be synthesized according to the following method:

[0025] (1) Prepolymerization: Add polymerization monomers hexamethylenediamine, adipic acid, terephthalic acid, end-capping agent benzoic acid and deionized water into a stainless steel autoclave equipped with mechanical stirring. After evacuating and replacing with N2 three times, start heating and stirring, raise the temperature to 180℃ at a rate of 5℃ / min, keep the temperature constant for 60min, then raise the temperature to 270℃ at a rate of 2℃ / min, stir slowly and keep the temperature constant for 4h to allow the prepolymerization reaction to proceed fully. After the constant temperature is completed, slowly raise the temperature to 280℃ and start draining to normal pressure. When the pressure drops to normal pressure, close the drain valve, the reaction is over, and the temperature drops to room temperature for discharge.

[0026] (2) Solid phase viscosity enhancement: The material prepared in the prepolymerization process is placed in a vacuum drum, the drum speed is set at 10 r / min, and the vacuum degree is set at 30 Pa. The temperature is increased at a rate of 20°C / min. When the temperature reaches 265°C, a sample is taken to test the viscosity, and the discharge end point is determined based on the viscosity result.

[0027] Preferably, the average diameter of the wollastonite in the PA6T66 molding composition is 8-17 μm, and the average length is 100-200 μm. Through experiments, it is found that the diameter and length of wollastonite do not decrease significantly under high temperature and high shear conditions in a twin-screw extruder.

[0028] The toner is selected from carbon black, black, or a mixture of various colors.

[0029] Preferably, the toner is selected from amorphous carbon toner.

[0030] Preferably, the whiteness of the polyamide molding composition is less than 25, and the reflectivity of the 460nm light source is less than 5%. More preferably, the reflectivity of the PA6T66 molding composition at 460nm light source is 2-3%.

[0031] By weight, it also includes 0-3 parts of antioxidant; the antioxidant is selected from at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphite antioxidants, thiol antioxidants, and thiodipropionate antioxidants.

[0032] The PA6T66 molding composition of the present invention is used for preparing a light source reflection bracket of an LED display screen.

[0033] The present invention has the following beneficial effects:

[0034] The reflectivity of the 460nm light source is mainly related to the surface roughness of the material (the larger the roughness of the surface of an object within a certain range, the more diffuse reflection of the light emitted by the light source on the surface of the object, and the less light energy received at the light receiving end) and the whiteness of the material (the lower the whiteness, the lower the reflectivity). The influence of the light source reflective bracket of the LED display screen on the grayscale and contrast of the LED display screen is mainly related to the whiteness and reflectivity of the light source reflective bracket. According to this principle, the PA6T66 molding composition of the present invention controls the whiteness to <30 and the reflectivity of the 460nm light source to <7% (improving grayscale and contrast) through the following three aspects, and has the advantages of good adhesion to hardware and low blue light of the packaged LED screen.

[0035] 1. Compared with other inorganic fillers, wollastonite can make the surface roughness of the polyamide molding composition reach a reasonable range to reduce light reflection, which not only reduces the reflectivity of the 460nm light source, but also improves the closeness with hardware. The preferred distribution size of wollastonite in the resin matrix can further reduce the reflectivity of the 460nm light source (reduce the blue light of the LED display) and improve the closeness with hardware.

[0036] 2. The color of the material is conditioned by the toner, and the black color has a good light absorption effect. The preferred non-oriented carbon toner can further reduce the whiteness and improve the light absorption, thereby reducing the reflectivity of the 460nm light source.

[0037] 3. The molar ratio of 6T / 66 units and the terminal amino content of PA6T66 resin cooperate with wollastonite to further improve the adhesion of surface roughness plating and hardware, and can reduce the amount of color powder added.

[0038] 4. The PA6T66 molding composition of the present invention does not require additional spraying of light-absorbing paint or frosting, thereby reducing the cost of the LED display light source bracket. DETAILED DESCRIPTION

[0039] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0040] The raw materials used in the embodiments and comparative examples are as follows:

[0041] PA6T66 resin-1: 6T unit content 45 mol%, terminal carboxyl content 38 mol / t, number average molecular weight 11000;

[0042] PA6T66 resin-2: 6T unit content 50 mol%, terminal carboxyl content 36 mol / t, number average molecular weight 10600;

[0043] PA6T66 resin-3: 6T unit content 55 mol%, terminal carboxyl content 70 mol / t, number average molecular weight 8400;

[0044] PA6T66 resin-4: 6T unit content 65 mol%, terminal carboxyl content 63 mol / t, number average molecular weight 9900;

[0045] PA6T66 resin-5: 6T unit content 50 mol%, terminal carboxyl content 40 mol / t, number average molecular weight 7200;

[0046] PA6T66 resin-6: 6T unit content 50 mol%, terminal carboxyl content 75 mol / t, number average molecular weight 14700;

[0047] PA6T66 resin-7: 6T unit content 50mol%, terminal carboxyl content 24mol / t, number average molecular weight 5800; PA6T66 resin-8: 6T unit content 50mol%, terminal carboxyl content 103mol / t, number average molecular weight 18000;

[0048] PA6T66 resin-9: 6T unit content 45 mol%, terminal carboxyl content 150 mol / t, number average molecular weight 8800;

[0049] PA6T66 resin-10: 6T unit content 40 mol%, terminal carboxyl content 105 mol / t, number average molecular weight 7500;

[0050] PA6T66 resin-11: 6T unit content 70 mol%, terminal carboxyl content 76 mol / t, number average molecular weight 7600;

[0051] Wollastonite A: average diameter, 17 μm, average length, 180 μm;

[0052] Wollastonite B: average diameter, 8 μm, average length, 110 μm;

[0053] Wollastonite C: average diameter, 4 μm, average length, 60 μm;

[0054] Wollastonite D: average diameter is 20 μm, average length is 210 μm.

[0055] Talc: AH-1250, Guangxi Longsheng Huamei Talc Development Co., Ltd.

[0056] Toner A: Amorphous carbon toner N774, Tianjin Tianyang Qiushi Chemical Technology Co., Ltd.;

[0057] Toner B: Carbon black M570, Cabot Chemical Co., Ltd.;

[0058] Toner C: Black UN2014, Cabot Chemical Co., Ltd.

[0059] Embodiment and comparative example PA6T66 molding composition preparation method: PA6T66 resin, wollastonite, color powder, antioxidant are added into a mixer and mixed evenly, and then extruded and granulated by a twin-screw extruder to obtain a polyamide molding composition; wherein the screw temperature range is 280-330°C and the rotation speed is 450r / min.

[0060] Test method:

[0061] (1) Number average molecular weight: The weight average molecular weight (Mw) and number average molecular weight (Mn) of PA6T66 resin samples were determined by gel permeation chromatography (GPC). Agilent HPLC-1260 high performance liquid chromatograph, equipped with: Eppendorf column oven, Shodex KF-801, 802, 802.5 and 803 gel permeation chromatography columns, differential detector, G7129A autosampler. Hexafluoroisopropanol was used as the mobile phase, and the molecular weight of the resin was determined at a column temperature of 40 °C. The data were processed using the chromatography workstation cirrus software to obtain the weight average molecular weight Mw and number average molecular weight distribution Mn.

[0062] (2) Adhesion: The PA6T66 molding composition sample was tested with red ink to characterize the adhesion between the bracket plastic and the hardware: The LED reflector cup formed by in-mold injection molding of the LED display light source bracket material and the electroplated hardware strip was immersed in red ink so that the red ink submerged the pins, and then left to observe whether the red ink penetrated into the reflector cup.

[0063] If the red ink does not penetrate into the reflective cup within 5 minutes, the density level is determined to be A;

[0064] If the red ink does not penetrate into the reflective cup after 3 minutes but penetrates into the reflective cup after 5 minutes, the density and grade are judged as B;

[0065] If the red ink does not penetrate into the reflective cup after 1 minute but penetrates after 3 minutes, the density level is determined to be C;

[0066] If the red ink penetrates into the reflective cup within 1 minute, the density level is determined to be D;

[0067] If the airtightness level is D, it means that the plastic and the hardware have poor airtightness, which may cause the lamp bead to fail. On the contrary, if the airtightness level is A, B, or C, the encapsulated lamp bead has excellent airtightness and good reliability.

[0068] (3) Whiteness: The contrast of the material is evaluated by the whiteness index of the material: a test piece with a length of 60 mm, a width of 60 mm and a thickness of 1 mm is prepared by injection molding the polyamide molding composition. The L, a and b values ​​are measured using a Color Eye 7000A colorimeter to calculate the whiteness:

[0069] W H =100-[(100-L) 2 +a 2 +b 2 ] 1 / 2 .

[0070] (4) Reflectivity: A test piece with a length of 60 mm, a width of 60 mm, and a thickness of 1 mm was prepared by injection molding the PA6T66 molding composition. The reflectivity of the test piece to light with a wavelength of 460 nm was measured using a Color Eye 7000A colorimeter.

[0071] Table 1: Examples 1-6 PA6T66 molding composition components (parts by weight) and test results

[0072]

[0073] It can be seen from Examples 1-6 that the whiteness and reflectivity are better when the amount of wollastonite is 40-55 parts.

[0074] Table 2: Examples 7-10 PA6T66 molding composition components (parts by weight) and test results

[0075]

[0076] It can be seen from Examples 7-10 that the reflectivity is better when the toner dosage is 1.2.

[0077] Table 3: Examples 11-17 PA6T66 molding composition components (parts by weight) and test results

[0078]

[0079] It can be seen from Examples 8 / 11 / 12 / 13 that wollastonite preferably has an average diameter of 8-17 μm and an average length of 100-200 μm.

[0080] It can be seen from Examples 8 / 14-17 that the toner is preferably a non-oriented carbon toner.

[0081] Table 4: Examples 18-25 PA6T66 molding composition components (parts by weight) and test results

[0082]

[0083] It can be seen from Examples 8 / 18-25 that the PA 6T66 resin preferably has a 6T unit content of 45-65 mol%, a number average molecular weight range of 7000-17000, and a terminal carboxyl content of 35-80 mol / t.

[0084] Table 5: Examples 26-28 PA6T66 molding composition components (parts by weight) and test results

[0085]

[0086] It can be seen from Examples 26-28 that the present invention adjusts the whiteness to less than 30 and the reflectivity to less than 7% by adding color powder and wollastonite, and obtains a PA6T66 molding composition that fits well with hardware.

[0087] Table 6: Comparative Example PA6T66 molding composition components (parts by weight) and test results

[0088] .

Claims

1. A PA6T66 molding composition, characterized in that: By weight, it includes the following components: 40-70 parts of PA6T66 resin; Wollastonite 30-60 parts; Color powder 0.4-5 parts; Based on the molar percentage of PA6T66, the 6T unit content is 45-65mol%, the 66 unit content is 35-55mol%, the terminal carboxyl content of the PA6T66 is 20-110 mol / t, and the number average molecular weight range is 7000-17000; The average diameter of wollastonite in the PA6T66 molding composition is 4-8 μm but not including 8 μm, and the average length is 10-100 μm but not including 100 μm; The whiteness of the PA6T66 molding composition is less than 30, and the reflectivity of the 460nm light source is less than 7%.

2. The PA6T66 molding composition according to claim 1, characterized in that The wollastonite content is 40-55 parts.

3. The PA6T66 molding composition according to claim 1, characterized in that Based on the molar percentage of PA6T66, the 6T unit content is 50-65 mol%, and the 66 unit content is 35-50 mol%.

4. The PA6T66 molding composition according to claim 1, characterized in that The terminal carboxyl content of the PA6T66 resin is 35-80 mol / t.

5. The PA6T66 molding composition according to claim 1, characterized in that The toner is selected from carbon black, black, or a mixture of various colors.

6. The PA6T66 molding composition according to claim 5, characterized in that: The toner is selected from amorphous carbon toner.

7. The PA6T66 molding composition according to claim 1, characterized in that The whiteness of the PA6T66 molding composition is less than 25, and the reflectivity of a 460nm light source is less than 5%.

8. The PA6T66 molding composition according to claim 7, characterized in that The PA6T66 molding composition has a reflectivity of 2-3% at 460 nm.

9. The PA6T66 molding composition according to claim 1, characterized in that By weight, it also includes 0-3 parts of antioxidant; the antioxidant is selected from at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphite antioxidants, thiol antioxidants, and thiodipropionate antioxidants.

10. Use of the PA6T66 molding composition according to any one of claims 1 to 9, characterized in that: Used to prepare LED display light source reflection bracket.

Citation Information

Patent Citations

  • Aromatic polyamide composition for molding

    JP2001106908A

  • Molding material for light reflector, light reflector and lighting apparatus

    JP2015074763A